2022
DOI: 10.1038/s41467-022-35041-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene activation guided by nascent RNA-bound transcription factors

Abstract: Technologies for gene activation are valuable tools for the study of gene functions and have a wide range of potential applications in bioengineering and medicine. In contrast to existing methods based on recruiting transcriptional modulators via DNA-binding proteins, we developed a strategy termed Narta (nascent RNA-guided transcriptional activation) to achieve gene activation by recruiting artificial transcription factors (aTFs) to transcription sites through nascent RNAs of the target gene. Using Narta, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 95 publications
1
0
1
Order By: Relevance
“…In each activation condition, we found that burst sizes of the corresponding target genes were increased (with, on average, log 2 FCs greater than 2) (Fig. 2e left), mirroring burst size observations discussed in the Narta activation protocol, which recruited artificial transcription factors to the transcription site [40]. In comparison, average splicing and degradation rate FCs were near zero (Fig.…”
Section: Kinetic Effects Of Perturbation On Transcriptionsupporting
confidence: 75%
“…In each activation condition, we found that burst sizes of the corresponding target genes were increased (with, on average, log 2 FCs greater than 2) (Fig. 2e left), mirroring burst size observations discussed in the Narta activation protocol, which recruited artificial transcription factors to the transcription site [40]. In comparison, average splicing and degradation rate FCs were near zero (Fig.…”
Section: Kinetic Effects Of Perturbation On Transcriptionsupporting
confidence: 75%
“…Therefore, the low efficiency of the construct expression with intronic MS2 repeats cannot be explained by changes in mRNA splicing dynamics. One study conducted in zebrafish used the MS2-MCP system as a way of recruiting artificial transcription factors to nascent mRNAs and reported that constructs with an intronic MS2 position function more efficiently than 3' ones (Liang et al, 2022). Nevertheless, in our experiments, intronic MS2 positioning did not yield the expected results, potentially due to other interfering factors discussed here.…”
Section: Discussioncontrasting
confidence: 58%